Young Leading Innovators and EU's R&D intensity gap - Michele Cincera; Reinhilde Veugelers (European Commission, Joint Research Centre (JRC), 2010)
Innovation in the European Union remains weak according to a number of key `input' indicators, especially R&D investment by the business sector, and there are relatively few signs of progress. From a firm-level perspective, Europe's innovation gap relative to the US results from an inappropriate industrial structure in which new firms do not play a significant role, especially in new high-tech sectors. This view of a structural EU innovation deficit has many supporters. But it has received little or no thorough empirical investigation. This paper aims to address this `evidence gap'. We find that compared to the US, the EU has fewer young firms among its leading innovators. But this accounts for only about one-third of the EU-US differential. The largest part of the differential is due to the fact that young leading innovators in the EU are less R&D intensive than their US counterparts. Further unravelling shows that this is almost entirely due to a different sectoral composition. We thus confirm that the EU-US private R&D gap is indeed mostly a structural issue.
Keywords: O32; 330; dynamics of firms; age of firms; EU-US R&D gap